Redox Regulation of T-Cell Function: From Molecular Mechanisms to Significance in Human Health and Disease - Kesarwani, Pravin (Mary Ann Liebert, Inc., 2013)
Reactive oxygen species (ROS) are thought to have effects on T-cell function and proliferation. Low concentrations of ROS in T cells are a prerequisite for cell survival, and increased ROS accumulation can lead to apoptosis/necrosis. The cellular redox state of a T cell can also affect T-cell receptor signaling, skewing the immune response. Various T-cell subsets have different redox statuses, and this differential ROS susceptibility could modulate the outcome of an immune response in various disease states. Recent advances in T-cell redox signaling reveal that ROS modulate signaling cascades such as the mitogen-activated protein kinase, phosphoinositide 3-kinase (PI3K)/AKT, and JAK/STAT pathways. Also, tumor microenvironments, chronic T-cell stimulation leading to replicative senescence, gender, and age affect T-cell susceptibility to ROS, thereby contributing to diverse immune outcomes. Antioxidants such as glutathione, thioredoxin, superoxide dismutase, and catalase balance cellular oxidative stress. T-cell redox states are also regulated by expression of various vitamins and dietary compounds. Changes in T-cell redox regulation may affect the pathogenesis of various human diseases. Many strategies to control oxidative stress have been employed for various diseases, including the use of active antioxidants from dietary products and pharmacologic or genetic engineering of antioxidant genes in T cells. Here, we discuss the existence of a complex web of molecules/factors that exogenously or endogenously affect oxidants, and we relate these molecules to potential therapeutics. Antioxid. Redox Signal. 18, 1497–1534.